2020
DOI: 10.3389/fmed.2020.00194
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polytrauma and Acute Respiratory Distress Syndrome on Markers of Fibrinolysis: A Prospective Pilot Study

Abstract: Acute respiratory distress syndrome (ARDS), which is associated with major morbidity and high mortality, is commonly developed by polytraumatized patients. Its pathogenesis is complex, and its development is difficult to anticipate, as candidate biomarkers for the prediction of ARDS were found not to be reliable for clinical use. In this prospective study, we assessed the serum antigen levels of tissue plasminogen activator (tPA) and plasminogen activator inhibitor type-1 (PAI-1) of 28 survivors of blunt polyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The limitations of our study include the fact that we based our sample size on the number of patients reported in published pilot studies [ 2 , 35 39 ] and did not perform an a priori power analysis. Furthermore, blood sampling was determined by the patient's willingness, thus resulting in an incomplete data set of enzyme levels for three survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of our study include the fact that we based our sample size on the number of patients reported in published pilot studies [ 2 , 35 39 ] and did not perform an a priori power analysis. Furthermore, blood sampling was determined by the patient's willingness, thus resulting in an incomplete data set of enzyme levels for three survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has a few limitations. Firstly, instead of performing an a priori power analysis, we based our sample size on the number of patients reported in published pilot studies [83][84][85][86][87][88]. Secondly, we could not provide a complete data set of serum protein levels for all survivors since the patient's willingness determined sampling.…”
Section: Plos Onementioning
confidence: 99%